Simulation of single phase induction motor fed by single phase AC to AC matrix converter / Muhamad Anas Mas'od - Mas'od, Muhamad Anas (2007)
This project focused on a model in Simulink which consists of Single Phase ac to ac Matrix Converter (SPMC), an Induction Motor and an ac Power Supply. This project also concerned with the process of current commutation in Single Phase Matrix Converter (SPMC). Simulation is performed using MATLAB in order to predict the behavior of Single Phase Induction Motor fed by Single Phase ac to ac Matrix Converter. The Sinusoidal Pulse Width Modulation (SPWM) is present as switching strategies to synthesize 50Hz output with IGBTs present as the power switching devices.